The Hate Speech Behavior of Teenagers on Social Media Instagram - Astuti, Firmina; Partini, P (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Purpose: The purpose of this study is to understand and describe the hate speech behavior of teenagers on social media Instagram. Methods: This research is a descriptive qualitative research. Data collection techniques in this study used an open questionnaires that were spread directly. Respondents of the study amounted to 40 people with the criteria of high school / vocational students, have an Instagram account and are willing to become research informants by filling out informed consent. Results: The results showed that the behavior shown by adolescents when they see content that contains elements of hate speech on Instagram, they just neglect the content, keep quiet, do not care, ignore the content and re-porting the content. Regarding the content of the hate speech accounts, some respondents claimed to have been affected by the contents of the hate speech accounts. The respondent stated that they had made hate speech comments on the account because they were affected by the contents, but there were respondents who stated that although they were affected by the contents of the account they never participated in hate speech. Related to disputes that often occur in the hate speech account’s comment section, all respondents believe that there is no need to get involved in such disputes. However, some respondents claimed to have been involved in disputes that occurred in the comments section on the hate speech account. Some of the respondents stated that they themselves were insulted because they were carried away by emotion, while other respondents claimed to only advise the person who started the dispute in the comments section and did not participate in the utterance of hatred. The factors that influence the behavior of hate speech in adolescents on Instagram are psychological or psychological condition of the offender, namely high temprament, as well as tools, facilities and technological advances. The impact of the hate speech received by the victim is the psychological impact in the form of negative emotions and positive emotions. These negative emotions include feeling angry, uncomfortable, sad, depressed, embarrassed, afraid, insecure, and hurt. While positive emotions are feeling uplifting.Value: Therefore, it is important to raise awareness about hate speech especially in social media so people can use social media in accordance with its function.